Social and labour conditions of colombian workers in Spain: between segmentation and precariousness - Bedoya Bedoya, María Rocío (Sociedad y Economía, 2010)
The purpose of this article is to answer the question on the conditions of workers labor partners Colombians who arrived in Spain in 2007 through the quota policy. It is argued that theories of segmented labor markets and regulation provide explanatory unemployment, temporary and precarious work. Interviews contrasted with the theoretical approaches proposed, we conclude that in the context of economic globalization favors the international competition of market economies, which takes place the phenomenon of migration, whose main cause of human mobility is home economics. It highlights the deterioration, the precariousness and the feminization of migration flows, such as current characteristics of workers who come to Spain through the quota policy.